Visceral infiltration of intrahepatic cholangiocarcinoma is most prognostic after curative resection - Retrospective cohort study of 102 consecutive liver resections from a single center. (July 2018) - Bartsch, Fabian; Baumgart, Janine; Hoppe-Lotichius, Maria; Schmidtmann, Irene; Heinrich, Stefan; Lang, Hauke
Abstract: Introduction: Intrahepatic cholangiocarcinoma (ICC) is a rare malignancy, and therefore large unicenter series on the surgical outcome are rare in the literature, and prognostic factors for overall survival in the literature vary widely. Methods: All patients who underwent surgery for ICC were prospectively recorded. The type of resection, operative details, histological results, morbidity, mortality, overall and recurrence-free survivals as well as prognostic factors were assessed. Prognostic factors were examined by univariate and multivariate analyses. P-values <0.05 were considered significant. Results: Between January 2008 and December 2015, 102 patients underwent a resection with curative intent and were included in this analysis. Major and extended hepatectomies were performed in 19 and 53 cases, respectively. Twenty-eight patients had additional vascular and 35 patients additional visceral resections. R0-resections were achieved in 87 patients (85.3%). Median recurrence-free and overall survivals were 9.3 and 20.8 months, respectively. N-stage, infiltration of surrounding structures and UICC stage were significant prognostic factors in the univariate analysis. Multivariate analysis depicted only visceral infiltration (p = 0.011) as independent predictor for overall survival, and tumor size (p < 0.001), N-stage (p = 0.007), R-stage (p = 0.008) and M-stage (p = 0.009) for recurrence-free survival. Conclusion: An aggressive surgical approach achieves a high rate of R0 resections even in advanced ICC. Visceral infiltration is an independent predictor for overall survival for ICC after curative resection. Highlights: An aggressive surgical approach achieves a high rate of R0 resections even in advanced ICC. Visceral infiltration is an independent predictor for OS for ICC after curative resection. N-stage, visceral infiltration and UICC stage were significant in the univariate analysis for OS. Tumor size, N-stage, R-stage and M-stage were independent predictors for RFS after resection of ICC.